Cultural Understanding of Non-timber Forest Products among the Babuban Community People of Eastern Nepal - Poudel, Jiban Mani (Occasional Papers in Sociology and Anthropology, 2010)
This paper presents a short analysis of human-nature relationship among the Bahuban community people of eastern Nepal based on the use of non-timber forest products (NTFPs1). The paper basically describes perceptions and understanding of different categories of people towards NTFPs based on symbolic meaning and use-value of these products in their lives. In addition, the paper also shortly discusses indigenous practices for NTFPs management in the study area. DOI: 10.3126/opsa.v11i0.3034 Occasional Papers in Sociology and Anthropology Vol.11 2009 126-147